Perinatal outcomes of singleton breech deliveries in a tertiary care centre in Nepal - Tamrakar, Renuka; Sitaula, Deekshanta; Sharma, Basant; Pokharel, Bandana; Khatri, Dhan; Pokharel, Sandip (Journal of Chitwan Medical College, 2021)
Background: Breech presentation has been associated with higher rates of perinatal morbidity irrespective of mode of delivery. The aim of this study was to determine the prevalence and perinatal outcomes of singleton breech deliveries at Chitwan Medical College, a tertiary level hospital in Nepal. Methods: A retrospective review of records of all women who delivered at Chitwan Medical College with breech presentation from September 2018 to October 2020 was conducted. Information on demographic variables, obstetric characteristics and perinatal outcomes were obtained, recorded and analyzed. Results: Out of 6712 cases of deliveries during the study period, 226 had breech presentation with prevalence of 3.37%. One hundred ninety-one (84.5%) of them had undergone Caesarean delivery with 125 (65.4%) emergency and 66 (34.6%) elective Caesarean delivery. More than two third (70.4%) of breech deliveries were term deliveries while 28.8% were preterm. There were 2 cases of still births and 1 neonatal death with Perinatal Mortality Rate of 13.27 per 1000 breech deliveries. Vaginal breech delivery was associated with higher perinatal mortality, low Apgar score and low birth weight. Caesarean breech delivery was associated with increased rates of Neonatal Intensive Care Unit admission. Conclusions: The neonatal mortality and morbidity were higher with the vaginal breech deliveries. However further studies with larger sample size and greater statistical power is necessary to draw definitive conclusion.